Kinetics of Phase Transformations During Cooling-Warming of Saccharomyces cerevisiae Cells in Alginate-Containing Cryoprotective Media - Ponomareva, Victoria L.; Kuleshova, Larisa G.; Vysekantsev, Igor P.; Onasenko, Olena S.; Mykhailova, Olga О. (Problems of Cryobiology and Cryomedicine, 2018)
The effect of sodium alginate on the viability and kinetics of phase transformations of Saccharomyces cerevisiae cells during cryopreservation was investigated. There were determined the optimal conditions for yeast cell cryopreservation such as: the cooling rate of 1 deg/min in alginate-containing cryoprotective media (cell viability of (90.79 ± 2.01)% and (88.11 ± 1.75)% in solution of 1% sodium alginate and in combination of 5% dimethyl sulfoxide (DMSO) and 1% sodium alginate, respect tively). Using cryomicroscopy, the presence of sodium alginate in cryoprotective medium was shown to change the crystallization performance and to shift the phase transition zone towards lower temperatures. The beginning of phase transformations in the specimens, cooled in 5% DMSO solution was recorded at –8.5°C, in those, containing 1% sodium alginate and in a three-component system, comprising the combination of 1% sodium alginate and 5% DMSO, it was found at –16 and –15°С, respectively. Probl Cryobiol Cryomed 2018; 28(3): 212–223